Relationship between threatened miscarriage and gestational diabetes mellitus - Hee Joong Lee; Errol Norwitz; Banghyun Lee (BMC, 2018)
Abstract Background Both threatened miscarriage and gestational diabetes mellitus (GDM) are common complications of pregnancy. However, only one pilot study has reported that these complications are not related. We aimed to investigate whether threatened miscarriage is one of the risk factors of GDM. Methods An unmatched case-control study of 1567 pregnant Korean women who underwent a two-step approach to diagnose GDM was retrospectively conducted. The eligible women were classified into normal (n = 840), borderline GDM (n = 480), and GDM (n = 247) groups. We analyzed the associations with threatened miscarriage in all groups with adjustment for confounding factors. Results The proportion of women who experienced threatened miscarriage was significantly lower in the GDM group than in the normal group (adjusted odds ratio (OR), 0.38; 95% confidence interval (CI), 0.18-0.78). It was significantly lower in the maternal hyperglycemia group (borderline GDM and GDM groups) than in the normal group (adjusted OR, 0.66; 95% CI, 0.47-0.91). The proportion of women who experienced threatened miscarriage was also significantly lower in the GDM group than in the normal (adjusted OR, 0.35; 95% CI, 0.17-0.70) and borderline GDM groups (adjusted OR, 0.46; 95% CI, 0.22-0.94). Moreover, the proportion of women who experienced threatened miscarriage significantly decreased according to the severity of glucose intolerance (adjusted OR, 0.94; 95% CI, 0.76-1.16). Conclusion This study demonstrates that threatened miscarriage is associated with decreased risk of GDM and the severity of glucose intolerance in Korean women. Additional studies are warranted to understand the pathophysiologic mechanisms that might exist between these frequent complications of pregnancy.